The presence and absence of gender and intersectionality in the 2023 NDIS review: a content analysis - Diana K. Piantedosi; Raelene Wilding; Maya G. Panisset; Léna I. Molnar; Chloe Bryant; El Gibbs; Anne-Maree Sawyer (International Journal for Equity in Health)
Abstract While a world-leading initiative, Australia’s National Disability Insurance Scheme (NDIS) has received criticism for its design and implementation. In particular, gender inequality in access to supports and services remains a significant issue. Was the 2023 NDIS Review successful in addressing the persistent problem of gender inequality? To answer this question, this paper presents a content analysis of key documents produced through the 2023 NDIS Review, to investigate whether and how gender inequality was acknowledged and integrated into the Review’s recommendations. The analysis assessed the frequency and conceptualisation of gender-related terms and of the Review’s preferred term, ‘intersectionality.’ The analysis found that the Review documents have limited references to gender-specific terms, often replacing them with ‘intersectionality’. However, this preferred term lacked an explicit definition and was operationalised inconsistently. Implied meanings were often diluted from the conceptual origins of intersectionality. This means that gender inequalities have been largely ignored in both the findings and recommendations. We conclude that the gendered foundation of issues is obscured by diluting interpretations of ‘intersectionality’ to the level of individuals or groups, which sideline systemic critique. Importantly, our article highlights the need for policy makers and researchers to operationalise the term ‘intersectionality’ deliberately and consistently.